Efektivitas Larutan Dekalsifikasi pada Os tibia Domba Garut (Ovis aries) (THE EFFECTIVENESS OF DECALCIFYING SOLUTIONS ON THE TIBIAL OF GARUT SHEEP (OVIS ARIES)) - Rakhmawati, Handina; Situmeang, Adrian; Nurhidayat, Nurhidayat; Lubis, Andri Maruli Tua; Murti, Harry; Boediono, Arief (Jurnal Veteriner; Vol 20 No 3 (2019)DO - 10.19087/jveteriner.2019.20.3.403, 2019)
Bone is a tissue that has a density of extracellular matrix structures and composed by organic and inorganic components. Decalcification is a stage that plays an important role in bone histology using various types of solutions. The sample used in this study was lateral condyle from tibia of three garut sheeps (Ovis aries) which had been fixed with 10% Neutral Buffered Formalin (NBF) for 24 hours. Sample were cut into pieces ranging from 1 cm x 1 cm x 1 cm in size, the decalcification using three solutions; 10% nitric acid, 10% EDTA (pH 7.4) and 10% EDTA (pH 7.4) + TBD-1®. The aim of this study was to evaluate the effectiveness of three solutions for the decalcification process of lateral tibial condyle of garut sheep. Observation parameter in this study includes: duration of decalcification, sectioning process of ribboning formation, structural integrity and absorption of hematoxylin-eosin (HE) staining. The results shows that 10% EDTA (pH 7.4) solution provides a long duration of decalcification which is ease sectioning process ribboning, the best structural integrity of lateral tibial condyle. In hematoxylin-eosin (HE) staining shows that 10% nitric acid solution does not absorb the optimum color, opposite in 10% EDTA and 10% EDTA + TBD-1® solution, the color intensity between hematoxylin and eosin in the tissue shows the best results. Based on these results, it can be concluded that the 10% EDTA (pH 7.4) is the best decalcification solution for lateral condyle from tibial of garut sheeps.